Development of organically modified montmorillonite/polypropylene composite powders for selective laser sintering - Tan, Lisa Jiaying (2020)
Organically modified montmorillonite/polypropylene (OMMT/PP) composite powders for selective laser sintering (SLS) were developed using four powder preparation methods including melt extrusion combined with cryogenic grinding, thermally induced phase separation (TIPS), surface coating, and mechanical mixing. Evaluations were conducted on the shape and size, powder-bed surface roughness, and thermal behavior of the developed composite powders as well as the mechanical properties of their injection-moulded tensile specimens. Melt extrusion proved to be the most favorable as the powders exhibited the highest thermo-oxidative stability (Td,max = 378 °C) and enhanced mechanical strength and ductility. TIPS could produce powders with reduced crystallization temperatures and increased melt enthalpies that were beneficial for SLS, and with powder morphology ideal for SLS without post-processing. It was found that at low loadings, nanofillers with sheet-like structures such as OMMT could limit the increase in crystallization temperatures of the composite powder, thus ensuring their wide sintering windows for SLS.